The association between CYP19 polymorphism and endometriosis risk: a system review and meta-analysis. (April 2016) - Yi, Ke; Yang, LingYun; Lan, Zhu; Xi, MingRong
Abstract: Objective: Endometriosis is a chronic, inflammatory, estrogen dependent disease. Genetic variation of estrogen biosynthesis and metabolic genes is associated with the risk of endometriosis. The CYP19 gene, encoding aromatase, plays an important role in the conversion of androgens to estrogens. Polymorphisms in the CYP19 gene are associated with circulating estrogen levels and estrogen/testosterone ratio. The aim of present study is to evaluate the impact of the CYP19 rs10046 polymorphism on endometriosis risk. Methods: Embase, PubMed and other databases were searched for eligible case–control studies. A fixed-effects or random effects model was appropriately selected to calculate the pooled odds ratios (ORs). Results: A total of 8 case–control studies including 993 cases and 1956 controls were available. Overall, the pooled results indicated that CYP19 rs10046 polymorphism was not associated with endometriosis risk (for heterozygous CC vs. CT carriers OR = 1.00, 95% CI: 0.82–1.21; for homozygous CC vs. TT carriers OR = 1.06, 95% CI: 0.83–1.35; allele contrast C vs. T OR = 1.01, 95% CI: 0.90–1.14; dominant model CC vs. CT + TT OR = 1.02, 95% CI: 0.85–1.23; recessive model CC + CT vs. TT OR = 1.05, 95% CI: 0.85–1.30). Heterogeneity among studies was founded in dominant model and allele contrast. Galbraith plot analyses were performed to assess the source of heterogeneity and one study was found to be contributor of heterogeneity. The heterogeneity decreased significantly after excluding that study. Conclusion: Present meta-analysis reveals that CYP19 rs10046 polymorphism may be not correlated to endometriosis risk.